Considering alternative reaction mechanisms: students' use of multiple representations to reason about mechanisms for a writing-to-learn assignment. Issue 2 (23rd February 2022) - Watts, Field M.; Park, Grace Y.; Petterson, Michael N.; Shultz, Ginger V.
Abstract : Organic reaction mechanisms are often represented by the electron-pushing formalism and reaction coordinate diagrams. These representations pose a challenge to students because valuable information is encoded within each representation, and students must know how to reason about mechanisms using both. Hence, it is important to understand whether and how students consider these two representations when reasoning about reaction mechanisms. We have collected responses to a writing-to-learn assignment administered in a second-semester organic chemistry laboratory course to investigate students' reasoning. The assignment was designed to elicit students' reasoning about the most likely of two mechanisms for a catalyzed intramolecular aldol reaction when given the electron-pushing scheme and reaction coordinate diagram for both mechanisms. As part of the assignment, students submitted initial drafts, participated in content-focused peer review, and submitted revised drafts. We analyzed each component using a mixed methods approach to identify students' reasoning about the most likely reaction pathway and how their reasoning changed after peer review and revision. In this article, we present a quantitative overview of changes students made about their decisions for the most likely reaction pathway and how these changes are related to providing and receiving feedback. Additionally, we present our analysis of the features of representations students used to reason about the likelihood of alternative reaction mechanisms. This study demonstrates how existing research about students' reasoning with representations was operationalized for classroom practice using writing-to-learn. Furthermore, the analysis illustrates how writing-to-learn to can be used to develop students' reasoning and offers implications for teaching students to reason about reaction mechanisms using multiple representations.